Factors Affecting Cash Holding in Indonesia Manufacturing Companies - Dewi Maya Sari; Dara Angreka Soufyan; Ainul Ridha (Jurnal Manajemen dan Keuangan, 2021)
This study aims to analyze the effect of leverage, net working capital, and firm size on cash holding using panel data regression method based on data on the financial statements of manufacturing companies available on the Indonesia Stock Exchange from 2012 to 2014. Testing with the Chow test states that the data regression model the panel used is the common effect. The results of this study indicate that cash holding is positively influenced by leverage, net working capital, and firm size. The greater the leverage, net working capital, and company size will increase the availability of cash in the company.